European Union Climate Governance and the European Green Deal in Turbulent Times - Dupont, Claire (2021)
In December 2019, the European Commission published the European Green Deal (EGD), an overarching policy framework to achieve climate neutrality in Europe by 2050. This thematic issue aims to understand the origins, form, development, and scope of the EGD and its policy areas. It uses the concept of turbulence to explore and assess the emergence of the EGD and the policy and governance choices associated with it. Focusing on different levels of governance, different policy domains, and different stages of policymaking, each contribution raises pertinent questions about the necessity of identifying sources of turbulence and of understanding how to govern with such turbulence, rather than against it. Overall, the articles in this issue demonstrate that, while specifying contextual factors, researching the sources of and responses to turbulence provides useful insights into the development, direction, and potential durability or advancement of EU climate governance.